Comparative Analysis of Economic Systems and Institutional Frameworks: A Cross-National Study - Hussein, Riyadh Rajab; Obaid, Siham Abd Ali; Baban, Omar; AbdulRahman, Mujahed Mutlaq (Journal of Ecohumanism, 2024)
Background: Comparative analysis of economic systems has received much interest, especially in understanding how institutional frameworks influence economic performance and development. The dynamism of global economies, exacerbated by the clash between capitalist and socialist ideals, needs a thorough assessment of the underlying mechanisms that control economic activity. Objective: The article aims to investigate the differences in economic outcomes caused by various economic systems and institutional configurations. It tries to understand the mechanisms by which institutions influence economic behavior, efficiency, and growth across different economic paradigms. Methods: Using a comparative analysis approach, this study examines various economic systems from qualitative and quantitative perspectives. Institutional economic theories govern the analysis of case studies, statistical data, and policy outcomes from various countries and economic models. The methodology includes econometric analysis to determine the patterns and effects of institutional arrangements on economic measures. Results: Preliminary data indicate a complex link between institutional architecture and economic outcomes. While market economies have strong development and innovation potential, state-led models have made tremendous social welfare and equity progress. The compatibility of institutional structures with cultural, historical, and social circumstances significantly impacts an economic system’s effectiveness. Conclusion: The article emphasizes the complexities of economic systems and institutions’ critical role in influencing economic trajectories. Considering the various institutional frameworks available, it calls for a personalized approach to economic policy creation. This study adds to the discussion on economic systems by providing insights for policymakers and scholars working toward sustainable and equitable economic development.